2012
DOI: 10.1002/hbm.22176
|View full text |Cite
|
Sign up to set email alerts
|

Specific frequency bands of amplitude low-frequency oscillation encodes personality

Abstract: The biological model of extraversion and neuroticism identified by Eysenck has stimulated increasing interest in uncovering neurobiological substrate of the two fundamental dimensions. Here we aim to explore brain disturbances underlying extraversion and neuroticism in 87 healthy individuals using fractional amplitude of low-frequency fluctuations (LFF) on resting-state functional magnetic resonance imaging. Two different frequency bands, Slow-5 (0.01-0.027 Hz) exhibiting higher power and involving larger brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 75 publications
6
66
4
1
Order By: Relevance
“…In addition, Slow-4 is more reliable and has greater test-retest reliability than Slow-5. A previous study has demonstrated a positive correlation between Slow-5 and extraversion in the midline core regions of the DMN [45] . In contrast, Slow-4 is negatively associated with extraversion in the lef t hippocampus, implying that the neuronal circuitry of emotion infl uences personality traits [45] .…”
Section: Amp Litude Of Low-frequency Fluctuationsmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, Slow-4 is more reliable and has greater test-retest reliability than Slow-5. A previous study has demonstrated a positive correlation between Slow-5 and extraversion in the midline core regions of the DMN [45] . In contrast, Slow-4 is negatively associated with extraversion in the lef t hippocampus, implying that the neuronal circuitry of emotion infl uences personality traits [45] .…”
Section: Amp Litude Of Low-frequency Fluctuationsmentioning
confidence: 79%
“…Slow-4 and Slow-5 have been identified as the primary ships with specific properties such as extraversion [44,45] .…”
Section: Amp Litude Of Low-frequency Fluctuationsmentioning
confidence: 99%
“…Previous studies have shown that extraversion is correlated with the rs-fMRI signal in the STG (Kumari, Williams, & Gray, 2004;Wei et al, 2014) and the thalamus (Kumari et al, 2004). Moreover, task-based fMRI studies have demonstrated that extraversion predicts the STG activity during humor appreciation (Mobbs, Hagan, Azim, Menon, & Reiss, 2005) and the thalamus activity in response to happy faces (Suslow et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…These discoveries may reflect the fact that individual frequency bands could be associated with specific properties (Buzsaki and Draguhn 2004). To date, the two frequency bands (slow-5 and slow-4) have been widely used in rs-fMRI studies when detecting the frequency distribution of spontaneous LFFs in BOLD signals of the human brain (Han et al 2011;Hou et al 2014;Wei et al 2014;Zhang et al 2013;Zuo et al 2010). Here, we aimed to explore the frequency distribution of spontaneous LFFs at specific frequency bands in MLPT newborns for the two different bands (slow-4 and slow-5).…”
Section: Introductionmentioning
confidence: 99%